La extracción de recursos mineros por empresas extranjeras y la privatización del poder coercitivo: un estudio de caso sobre la empresa de seguridad Forza - Kamphuis, Charis (2011)
This paper explores the reorganization of security and coercive power in Peru in response to the needs of foreign owned mining companies in an environment of social protest and opposition. It begins with an analytical description of the domestic legal regime that structures security services in Peru. In this context, a case study of Forza is undertaken. Forza is one of Peru’s oldest and most powerful private security companies, recently purchased by a transnational security services corporation. Forza’s human rights record is explored through three on-going cases: the Majaz Case, the Grufides Case and the Business Track Case. These cases signal a deep interpenetration of the economic and political power of foreign-owned mining companies, Forza and the Peruvian justice system. The paper then analyzes the Forza case study in terms of the applicable systems of international and domestic law. At the domestic level, these consist of the Peruvian domestic legal system and investors’ home state legal systems. At the international level, three distinct normative systems are similarly considered: public international human rights law, private international foreign investment law, and corporate social responsibility mechanisms. This overview provides some insight into how the «global gap» in the enforcement of domestic law and the asymmetry in the enforcement of international law function together to produce the conditions of impunity in the Forza case study. The paper concludes by proposing a methodological approach to international lawyering and legal academic work in relation to social movements responding to resource extraction activities.